Role of chemokine-like factor 1 as an inflammatory marker in diseases - Li, Yutong; Yu, Haiyang; Feng, Juan (Frontiers in Immunology, 2023)
Immunoinflammatory mechanisms have been incrementally found to be involved in the pathogenesis of multiple diseases, with chemokines being the main drivers of immune cell infiltration in the inflammatory response. Chemokine-like factor 1 (CKLF1), a novel chemokine, is highly expressed in the human peripheral blood leukocytes and exerts broad-spectrum chemotactic and pro-proliferative effects by activating multiple downstream signaling pathways upon binding to its functional receptors. Furthermore, the relationship between CKLF1 overexpression and various systemic diseases has been demonstrated in both in vivo and in vitro experiments. In this context, it is promising that clarifying the downstream mechanism of CKLF1 and identifying its upstream regulatory sites can yield new strategies for targeted therapeutics of immunoinflammatory diseases.